Double disadvantage? The slow progress of non-English-speaking migrant women in accessing good jobs in Australia. (2nd July 2020) - Haque, Tariq H.; Haque, M. Ohidul
ABSTRACT: In this paper, primary and secondary sector employment corresponds broadly to 'good' and 'bad' jobs. Previous studies indicate that non-English-speaking background (NESB) migrant women are under-represented in 'good jobs' but none of those studies evaluates their chance of finding 'good jobs' in Australia. This study estimates their probability of getting good jobs and compares this with that of Australian-born women. The probability of securing good jobs for each of these groups is also estimated separately, based on a new general probit model, after classifying women into primary and secondary sector employment from their occupational categories and incomes using 2016 Australian Census data. It showed that NESB migrant women had significantly lesser probability of securing primary sector employment compared to Australian-born women. While this difference is narrowing over time, NESB migrant women's progress in accessing 'good jobs' has been slow. Improving English proficiency, education, recognition of overseas qualifications and experience can significantly increase their chances of attaining good jobs. This study provides an exact estimate of the probability of securing good jobs for both groups and the relevance of different determinants for this difference so that proper actions can be taken to improve the employment situation of NESB migrant women.